Stature estimation in Malaysian population from radiographic measurements of upper limbs - Normaizatul Afizah Ismail; Norakmal Hisyam Abd Khupur; Khairul Osman; Ab Halim Mansar; Mohamed Swarhib Shafie; Faridah Mohd Nor (Egyptian Journal of Forensic Sciences, 2018)
Abstract Background Stature is one of the important aspects of biological profile for an unknown individual in forensic anthropology. As stature is population-specific, this study was conducted in Hospital Sungai Buloh, Hospital Tapah and Hospital Kampar to develop regression for stature estimation in the Malaysian population. About 90 subjects from 23 to 47 years old were selected for radiography of upper limbs. The standing height of the subject was measured beforehand for each subject. The maximum length of the bones was measured on the x-ray film in cm, and analysis was performed by SPSS version 23. Results Results showed significant correlations between stature and upper limb bones (p < 0.05). There was significant difference between males and females in stature (p < 0.05). However, there was no significant difference found in stature among age and demic groups (p > 0.05). About eight regression equations were developed, of which three for single bone and one in combination of three bones in males and females. The regression equations with combination of bones showed the highest correlation coefficient (r). However, these regression equations are not suitable yet to be used practically in Malaysian population due to high standard error of estimates. Conclusion In brief, the research study has to be validated with a larger sample size to represent the Malaysian population.